Overcoming doubt in vaccinations. The end justifies the means? - Ciliberti, Rosella; Licata, Marta; Larentis, Omar (Acta Biomedica Atenei Parmensis, 2022)
Controversies and skepticism about vaccination have existed as long as vaccination itself. Today and yesterday, the authority of religious leaders has a fundamental role to convince members of their congregations to accept or reject vaccination. Our contribution tells of the stratagem used by the Italian doctor Luigi Sacco to make the faithful lean towards the vaccination using their faith as a means. The history of yesterday’s end of today opens a current debate on the role and responsibility of religion around vaccination practice. As COVID-19 vaccine mandates grow, so are requests for religious exemptions.